Integrating flare gas with cogeneration system: Hazard identification using process simulation. (January 2022) - Sarkar, Sankhadeep; Quddus, Noor; Mannan, M. Sam; El-Halwagi, Mahmoud M.
Abstract: Flare gas integration with a cogeneration plant benefits from utilizing waste gases containing high heating value hydrocarbons as a supplemental fuel to the boilers. A key challenge in integrating flare gas with a cogeneration system is the need to ensure operational safety and satisfactory performance. Conventional hazard identification techniques require collective team knowledge, experience, and information about the process. Because of the limited information on a new flare gas integrated cogeneration plant, unawareness of warning signals, inability to predicts specific atypical scenarios, or general limitations in organizational systems, it is possible for the evaluation team to miss potential risks associated with the process. To overcome these limitations, this paper proposes a model to identify process hazards through process simulation, sensitivity analysis, and data evaluation during the initial stages of process design. The model uses commercial software Aspen HYSYS for process simulation. In sensitivity analysis, manipulated variables are systematically selected based on scenario predictive methods, and the variations in the processes are analyzed using linear regression models to develop quantitative insights without information loss. The model investigated the effect of variable flare gas conditions and their quality on the existing fired gas boiler. Results showed that the flare gas temperature has a nominal effect on the process. However, changes in flare gas composition - high hydrogen carryover (above 70 mol% with CH4 or above 40 mol% with C2 H4 ) can affect the boilers radiation zone temperature and combustion profile inside the firebox. If not prevented, these events can further amplify to loss-control events such as flame impingement, firebox instability, steam explosion, and tube rupture. Highlights: Hazards of flare gas integration with cogeneration identified by process simulation. Effect of flare gas conditions and quality under abnormal situation investigated. Any changes in flare gas quality affect boiler operating conditions significantly. Top events have major influences on operational time and mechanical integrity.